Synthesis, Cholesterolmic Activity of Formamidinoisothio Amides - PANDEYA, S.N.; SHUKLA, S.K.; SINGH, B.N. (Asian Journal of Chemistry, 2010)
In the present paper, the synthesis and cholesterolmic activity of formamidino isothio amides has been studied.